FENOMENA KLASIK PADA TINGGALAN ARKEOLOGIS DARI MASA KERAJAAN DEMAK DI DESA PRAWOTO - Inagurasi, Libra Hari (BRIN, 2001)
At Prawoto Hill there is a classical-Hindu phenomenon even though it is within the historical framework of the Islamic Kingdom of Demak. This classical-Hindu phenomenon can be seen in the archaeological remains and the concept behind the choice of Hill or Mount Prawoto as a place to build a pesanggrahan building. Yoni, and statues still colored the construction of the pesanggrahan building during the Demak Kingdom era, but their function had been transferred from sacred to religious to profane. The concept of mountains is a concept that has existed since the classical-Hindu period and still has an important meaning during the era of the Demak Kingdom.